Islamic Fundraising: Increasing Donor Participation in the Development of Islamic Educational Institutions - Eneng Muslihah; Euis Asyiah; Supianto; Bayu Pramono (Didaktika: Jurnal Kependidikan, 2025)
This study examines the implementation of Islamic fundraising strategies to enhance donor participation in the development of Islamic educational institutions. In the context of globalization and increasing competition, Islamic educational institutions often face financial constraints that hinder educational development and quality. Through a qualitative approach based on a comprehensive literature review, this research analyzes the concepts, methods, and principles of Islamic fundraising and their impact on Islamic educational institutions. The findings indicate that Islamic fundraising, rooted in the Quran and Hadith, is not only effective in raising funds but also strengthens Islamic identity and values in education. Direct and indirect fundraising methods, combined with strategies such as face-to-face interactions, direct mail, special events, and campaigns, prove to increase donor participation. Principles such as education, ethics, professionalism, and transparency are key to building donor trust and loyalty. Significant impacts of implementing Islamic fundraising include increased financial resources, donor satisfaction, positive institutional image, and encouragement of innovation and creativity in the educational environment. This study concludes that integrated and technology-based Islamic fundraising strategies can effectively enhance donor participation and support the sustainability of Islamic educational institutions. Recommendations for future research include exploring innovative fundraising strategies and improving inter-institutional collaboration to create a sustainable Islamic education ecosystem. The study also finds that the financial independence of Islamic educational institutions through income diversification and operational efficiency is crucial to complement Islamic fundraising strategies.